PENINGKATAN MUTU PENDIDIKAN BERBASIS MANAJEMEN SEKOLAH MODEL - Muhammad Hafid Fadillah; Syamsu Sanusi; Efendi P. (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
The research aims to know the improvement of education quality model school management based and to find out the the supporting and inhibiting factor in improving education quality model school management based. This research is qualitative research with descriptive analysis. The data was collected by observation, interview, and documentation. Data was analyzed through collecting data, data reducation, data display, and conclusion. The quality improvement model school management based in SMP N 8 Palopo has fulfilled eight quality standar by preferring five steps those are analyzing model school quality development data, analyzing root problem of model school development, planning model school quality development, and the imrpvement implementation of model school qualitydevelopment. The supporting factors of model school management based improvement are the principal leadership, creating well competention for teachers and students, and school guidance in improving school quality. The inhabitation factors are school environment, teachers, education quality and a number of teacher school activities.